Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak ( Studi Kasus pada Wajib Pajak Orang Pribadi dan Badan di Wilayah Kota Jambi - Wirmie Eka Putra; Indra Lila Kusuma; Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2019)
This study aims to examine the effect of tax amnesty, knowledge of taxation, tax services and tax sanctions on taxpayer compliance. The sampling technique that will be used in this study is purposive sampling technique. Primary data is collected by distributing questionnaires. The research sample was 45 respondents of individual and body taxpayers found in Jambi City Region. Data analysis techniques in this study are descriptive statistics and multiple regression analysis. The software used for data processing is SPSS version 21 for Windows. The results of testing the hypothesis are as follows. Simultaneously, tax amnesty, knowledge of taxation, tax authorities and tax sanctions affect taxpayer compliance. Partially, tax amnesty, knowledge of taxation on taxation sanctions has an effect on taxpayer compliance and service of tax authorities has no effect.